Genetic analysis of tuber yield and quality traits in white yam (Dioscorea rotundata Poir) - Norman, P.E.; Asfaw, A.A. (University of Ghana, 2019)
The genetic progress in tuber yield and quality attributes of yam is constrained by prolonged breeding cycle, complex ploidy (2n=40, 60, 80), high heterozygousity, complex flowering pattern (dioecois and monoecious flowering and shy to flower), multi-species, low propagation ratio, biotic and abiotic factors. Genetic improvement of yam with high tuber yield, high dry matter content, starch and other food quality attributes using traditional and modern breeding techniques will contribute to the sustainable food production. The objectives of this study were to (i) determine molecular and phenotypic trait values of yam progenitors used for crop improvement; (ii) assess the degree of pollination success under two mating schemes; (iii) assess the potential of parentage analysis in half-sib breeding pipeline for effectively building the relationships among progenies and their parents in yam polycross; (iv) assess within and between family variation for growth and yield attributes of seed progenies at early generation breeding stages; (v) estimate genetic parameters and identify key traits for germplasm evaluation in white yam breeding trials using molecular marker information; and (vi) determine the magnitude of genotype by environment interaction for genetic improvement of important traits in white yam. Thirty-six white yam (Dioscorea rotundata) trait progenitors were profiled for phenotypic attributes and their genetic merits using SNP genotyping. The 48 traits measured in the 36 clones showed medium (r=0.61) to high (r=0.99) prediction accuracy, narrow sense heritability (from 0 to 0.99), and broad sense heritability (from 0 to 0.98). These findings are useful for yam population improvement, selection of genotypes for short release programme as well as genetic conservation of valuable germplasm. The analysis for breeding value identified potential parents for population improvement as well as superior candidates for short realese programme. Pollination success using selected trait progenitors (three males and nine females) under controlled and open natural pollination schemes indicated high variability in filled seeds in polycross (R2=0.67; p<0.05) than controlled hand pollination (R2=0.40; p=0.301). High pollination events and subsequent fruiting success contributed to the higher filled seed production with the polycross mating. Paternity test and seedling traits assessment in white yam (Dioscorea rotundata) progenies generated using controlled and open pollinated polycross mating designs revealed that progenies that are genetically related are grouped and traced to their putative parents. The successful application of paternity test helps to reconstruct pedigree and exploit the potential of half-sib breeding in yam. The within and between family variabilities were significant for all the seedling traits. Analysis for agronomic and quality traits on 49 advanced yam clones grown at multi-location trials using mixed model employing genomic relationship matrix identified genotypes TDr09/00135, TDr10/00412, TDr09/00052, TDr89/00983 and TDr11/00291 as potential parents for recycling in breeding and / or candidates for release as new varieties. The significant genotype by environment interactions for the key traits measured in advanced yam clones indicated the necessity of testing the genotypes in multiple environments for effective selection and recommendation for release. The results on the successful paternal reconstruction of half-sib progenies of yam are relevant for pedigree identification, accurate dissection of the genetic effects and selection of clones. This would contribute to accurate prediction of the extent of gene flow in heterogeneous populations of yams. Moreover, the genotypes identified with desired trait values (high yield, dry matter content and quality traits) should be extensively tested and promoted for adoption and commercial deployment.